Are metals involved in tattoo‐related hypersensitivity reactions? A case report. (9th August 2017) - de Cuyper, Christa; Lodewick, Evelyne; Schreiver, Ines; Hesse, Bernhard; Seim, Christian; Castillo‐Michel, Hiram; Laux, Peter; Luch, Andreas
Summary: Background: Allergic reactions to tattoos are not uncommon. However, identification of the culprit allergen(s) remains challenging. Objectives: We present a patient with papulo‐nodular infiltration of 20‐year‐old tattoos associated with systemic symptoms that disappeared within a week after surgical removal of metal osteosynthesis implants from his spine. We aimed to explore the causal relationship between the metal implants and the patient's clinical presentation. Methods: Metal implants and a skin biopsy of a reactive tattoo were analysed for elemental contents by inductively coupled plasma mass spectrometry and synchrotron‐based X‐ray fluorescence (XRF) spectroscopy. Results: Nickel (Ni) and chromium (Cr) as well as high levels of titanium (Ti) and aluminium were detected in both the skin biopsy and the implants. XRF analyses identified Cr(III), with Cr(VI) being absent. Patch testing gave negative results for Ni and Cr. However, patch tests with an extract of the implants and metallic Ti on the tattooed skin evoked flare‐up of the symptoms. Conclusion: The patient's hypersensitivity reaction and its spontaneous remission after removal of the implants indicate that Ti, possibly along with some of the other metals detected, could have played a major role in this particular case of tattoo‐related allergy.